Short-term synaptic plasticity in the nociceptive thalamic-anterior cingulate pathway - Vogt Brent A; Shyu Bai-Chuang (SAGE Publishing, 2009)
Abstract Background Although the mechanisms of short- and long-term potentiation of nociceptive-evoked responses are well known in the spinal cord, including central sensitization, there has been a growing body of information on such events in the cerebral cortex. In view of the importance of anterior cingulate cortex (ACC) in chronic pain conditions, this review considers neuronal plasticities in the thalamocingulate pathway that may be the earliest changes associated with such syndromes. Results A single nociceptive electrical stimulus to the sciatic nerve induced a prominent sink current in the layer II/III of the ACC in vivo, while high frequency stimulation potentiated the response of this current. Paired-pulse facilitation by electrical stimulation of midline, mediodorsal and intralaminar thalamic nuclei (MITN) suggesting that the MITN projection to ACC mediates the nociceptive short-term plasticity. The short-term synaptic plasticities were evaluated for different inputs in vitro where the medial thalamic and contralateral corpus callosum afferents were compared. Stimulation of the mediodorsal afferent evoked a stronger short-term synaptic plasticity and effectively transferred the bursting thalamic activity to cingulate cortex that was not true for contralateral stimulation. This short-term enhancement of synaptic transmission was mediated by polysynaptic pathways and NMDA receptors. Layer II/III neurons of the ACC express a short-term plasticity that involves glutamate and presynaptic calcium influx and is an important mechanism of the short-term plasticity. Conclusion The potentiation of ACC neuronal activity induced by thalamic bursting suggest that short-term synaptic plasticities enable the processing of nociceptive information from the medial thalamus and this temporal response variability is particularly important in pain because temporal maintenance of the response supports cortical integration and memory formation related to noxious events. Moreover, these modifications of cingulate synapses appear to regulate afferent signals that may be important to the transition from acute to chronic pain conditions associated with persistent peripheral noxious stimulation. Enhanced and maintained nociceptive activities in cingulate cortex, therefore, can become adverse and it will be important to learn how to regulate such changes in thalamic firing patterns that transmit nociceptive information to ACC in early stages of chronic pain.